ANALISIS PENGEMBANGAN DAN PEMANFAATAN PEMBIAYAAN DAERAH DAN PENGARUHNYA TERHADAP PENDAPATAN ASLI DAERAH DI PEMERINTAH KOTA KUPANG - Pattimau, Andrianus (Jurnal Ilmiah Akuntansi dan Keuangan (JIAKu), 2024)
This research aims to determine the development and utilization of regional financing and its influence on Regional Original Income. This research was conducted at the Kupang City Regional Financial and Asset Agency, using statistical regression analysis tests to determine and test the relationship and/or influence of capital participation on local original income. Based on the test, it is concluded that; 1) Permanent regional capital (investment) participation for five years experienced an increase that was not constant or experienced fluctuations. The conclusion is drawn that the regional capital participation (investment) which has a permanent positive effect on regional original income is rejected; 2) Non-permanent regional capital (investment) participation does not involve non-permanent regional capital (investment) every year. The conclusion is drawn that there is an insignificant influence between non-permanent regional capital participation (investment) and regional original income; 3) Permanent and non-permanent regional capital participation (investment) for nine years has experienced an increase that is not constant or fluctuating. The conclusion is drawn that permanent and non-permanent regional capital participation (investment) together have no effect on regional original income; and 4) Based on data analysis using LINDO version 19.0, that the regional capital participation (investment) only focuses on two companies (Bank NTT and PDAM Kupang City), so it has not been able to make a large contribution to locally-generated revenue.